Legal Analysis Of Authority On Military Judges In Judging Of Indonesian National Army (TNI) - Sarjono Sarjono; Umar Ma'ruf (Law Development Journal, 2021)
This study aims to find answers to three problems. First, because members of the TNI or TNI soldiers who commit general crimes are not tried in civil courts. Second, the authority of the Military Court to try TNI soldiers who commit general crimes after the enactment of Act No. 34 Th. 2004 regarding the TNI. Third, the obstacles/solutions to law enforcement in prosecuting TNI soldiers after the enactment of the TNI Law. This study uses a normative juridical approach, using primary legal materials and secondary legal materials. The results of the study show that, firstly, TNI members who commit criminal acts are not tried in the Civil Court because there has been no amendment to Act No. 31 of 1997 concerning Military Courts, secondly that after the enactment of Act No.